Clinical magnetocardiography: the unshielded bet—past, present, and future - Brisinda, D.; Fenici, P.; Fenici, R. (Frontiers in Cardiovascular Medicine, 2023)
Magnetocardiography, nowadays sixty-year-old, has not yet been fully accepted as a clinical tool. Nevertheless, a large body of research and several clinical trials have demonstrated its reliability in providing additional diagnostic electrophysiological information if compared to conventional noninvasive electrocardiographic methods. Since the beginning, one major objective difficulty has been the need to clean the weak cardiac magnetic signals from the much higher environmental noise, especially that of urban and hospital environments. The obvious solution to record the magnetocardiogram in highly performant magnetically shielded rooms has provided the ideal set-up for decades of research demonstrating the diagnostic potential of this technology. However, only a few clinical institutions have had the resources to install and run routinely such highly expensive and technically demanding systems. Therefore, increasing attempts have been made to develop cheaper alternatives to improve the magnetic signal-to-noise ratio allowing magnetocardiography in unshielded hospital environments. In this article, the most relevant milestones in the magnetocardiography's journey are reviewed, addressing the possible reasons beyond the currently long-lasting difficulty to reach a clinical breakthrough, leveraging the Authors' personal experience since the early eighties attempting to and finally bringing magnetocardiography to the patient's bedside for many years thus far. Their nearly four decades of foundational experimental and clinical research between shielded and unshielded solutions are summarized and referenced, following the original vision that magnetocardiography had to be intended as an unrivaled method for contactless assessment of the cardiac electrophysiology and as an advanced method for non-invasive electroanatomical imaging, through multimodal integration with other non-fluoroscopic imaging techniques. Whereas all the above accounts for the past, the present demonstrates that, with the available innovative sensors, and more affordable active shielding technologies, several novel systems have been developed and tested in multicenter clinical trials adopting both shielded and unshielded magnetocardiography built-in hospital environments. The future of MCG will mostly be dependent on the results from the ongoing progress in novel sensors technology, which is foreseen to provide relatively soon multiple alternatives for the construction of more compact, affordable, portable, and even wearable devices for unshielded magnetocardiography inside hospital environments and perhaps also of ambulatory patients.